Sa kagabhion sa Sendong = On the night of Sendong narratives of children-survivors - De La Pena, Lilian C.; De Torres, Amor Q. (Cagayan de Oro City Capitol University Press, 2012)
"This collection of stories by fourteen children survivors of Sendong contributes to our understanding of disaster and to our efforts of finding the best and effective ways to minimize disaster's impact. The belief that great disasters, such as Sendong, come only after every fifty years is challenged now by the frequent occurence of disasters. The nature and magnitude of disasters now and its destructive aftermath have significantly changed, and which current disaster preparedness systems are unfit to respond..."
This book is dedicated to all the children who struggled to save their lives and that of their families from Sendong on December 16-17, 2011 in the cities of Cagayan de Oro, and Iligan.--Title page.
Narratives in Sebuano.
Keywords: Child disaster victims -- Philippines -- Cagayan De Oro City -- Personal narratives; Typhoons -- Philippines -- Cagayan De Oro City